Aprepitant in the Treatment of Subacute Sclerosing Panencephalitis: A Randomized, Double-Blind, Placebo-Controlled Study - ARMAN KANDIRMAZ, EMİNE; SANCAR, MESUT; TEZCAN, SONGÜL (ELSEVIER SCIENCE INC, 2020)
Background: Aprepitant is a neurokinin-1 receptor antagonist approved for the treatment of chemotherapy-induced nausea. We aimed to investigate the safety and efficacy of aprepitant in patients with subacute sclerosing panencephalitis. Methods: A randomized, double-blind, placebo-controlled study was conducted in patients with subacute sclerosing panencephalitis assigned to receive two courses of aprepitant 250 mg/day orally or placebo for 15 days with an interval of two months between courses. Primary end points were safety and tolerability, and secondary end point was clinical improvement or stabilization assessed by subacute sclerosing panencephalitis scoring system. Electroencephalography (EEG), brain magnetic resonance imaging, and cerebrospinal fluid measles-specific immunoglobulin G index were evaluated before and after treatment. Results: Sixty-two patients with subacute sclerosing panencephalitis were allocated to aprepitant (n = 31, median age 18 years) or placebo (n = 31, median age 22 years) group. Fifteen patients left the study within the first six months and 12 patients left between six and 12 months. Aprepitant was well tolerated and treatment-associated adverse events were similar to those described in the treatment of nausea. Clinical status at six and 12 months' follow-up did not differ between aprepitant and placebo groups. Post-treatment EEG scores at 12 months were better in the aprepitant group (P = 0.015). Cerebral atrophy on magnetic resonance imaging increased in both groups, whereas measles-specific immunoglobulin G index decreased in the placebo group. Conclusions: In this first clinical trial of aprepitant treatment in patients with subacute sclerosing pan encephalitis, the drug was safe and well tolerated. No clinical effect was observed. A modest improvement in EEG findings might justify trials for longer periods because EEG changes can precede clinical findings in subacute sclerosing panencephalitis. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Subacute sclerosing panencephalitis; Neurokinin-1 receptor; Aprepitant; Measles virus; SSPE; CEREBROSPINAL-FLUID; SSPE